Формування інформаційно-мережевого цифрового суспільства: ключові аспекти цифрової економіки - Дубницький, В.І.; Писарькова, В.Р.; Мішустіна, Т.С. (Вісник економічної науки України, 2025)
У статті проаналізовано цифрову економіку як новий етап еволюції соціально-економічних систем. Розглянуто ключові особливості переходу від постіндустріального до інформаційно-мережевого цифрового суспільства та вплив когнітивних технологій, цифрових платформ та інтернету речей на бізнес-моделі, споживчу поведінку та організаційні структури. Значну увагу приділено формуванню цифрової культури та розвитку бізнес-екосистем. У роботі показано, що тотальна цифровізація, впровадження ІКТ і технологій штучного інтелекту є природним і закономірним процесом, а отже – неминучим. Встановлено, що парадигмі цифровізації притаманні як позитивні, так і негативні ефекти. Результати дослідження можуть бути використані при розробці програм і стратегій розвитку та реалізації процесу цифрової трансформації економіки. This article presents a comprehensive analysis of the digital economy as a distinct stage in the evolutionary development of socio-economic systems. The authors argue that the digital economy represents a fundamental transformation of both technological and institutional foundations of modern society, rather than a simple continuation of post-industrial dynamics. The study offers a historical and conceptual overview of economic development stages shaped by technological revolutions – agrarian, industrial, post-industrial, and digital – and emphasizes the unique characteristics of the current information-network era. Through a synthesis of theoretical approaches and empirical observations, the paper explores how digital technologies – especially cognitive technologies, big data, artificial intelligence, and the Internet of Things – redefine traditional economic paradigms, production-consumption chains, and value creation mechanisms. Special focus is given to the rise of digital business ecosystems that increasingly replace linear supply chains and hierarchical corporate models. These ecosystems are built on platform-based interaction, accelerated knowledge exchange, and the reduction of transaction costs. The article also highlights the importance of digital culture as a transformative factor influencing behavioral patterns, institutional practices, and the adaptation of economic agents to rapidly changing digital environments. The authors argue that digitalization fosters not only new forms of entrepreneurship and employment but also poses serious risks, including deepening socio-economic inequality, erosion of privacy, cyber threats, and disruption of traditional labor markets. The case of Ukraine is used as a context-specific illustration of the complexities of digital transformation under conditions of economic crisis and geopolitical instability. Despite infrastructural and institutional constraints, the digitalization of Ukraine’s economy is considered a strategic priority, with potential for accelerated development through public-private collaboration, increased digital literacy, and integration into global innovation ecosystems. The paper concludes that the success of digital transformation depends on ensuring national digital sovereignty, fostering inclusive growth, and aligning digital development with the principles of the sixth and upcoming seventh technological paradigms.